2020
DOI: 10.3390/microorganisms8020212
|View full text |Cite
|
Sign up to set email alerts
|

Proposing BCG Vaccination for Mycobacterium avium ss. paratuberculosis (MAP) Associated Autoimmune Diseases

Abstract: Bacille Calmette–Guerin (BCG) vaccination is widely practiced around the world to protect against the mycobacterial infection tuberculosis. BCG is also effective against the pathogenic mycobacteria that cause leprosy and Buruli’s ulcer. BCG is part of the standard of care for bladder cancer where, when given as an intravesicular irrigant, BCG acts as an immunomodulating agent and lessens the risk of recurrence. Mycobacterium avium ss. paratuberculosis (MAP) causes a fatal enteritis of ruminant animals and is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 158 publications
(173 reference statements)
0
21
0
Order By: Relevance
“…paratuberculosis (MAP) in AD [31]. It is notable that the ongoing BCG clinical trials for autoimmune diabetes and multiple sclerosis are both diseases associated with MAP [32].…”
Section: Discussionmentioning
confidence: 99%
“…paratuberculosis (MAP) in AD [31]. It is notable that the ongoing BCG clinical trials for autoimmune diabetes and multiple sclerosis are both diseases associated with MAP [32].…”
Section: Discussionmentioning
confidence: 99%
“…BCG vaccine achieves this effect by inducing pattern recognition receptor NOD2, resulting in metabolic changes with epigenetic rewiring [5]. The reasoning behind the initiating of this process is immunomodulation [6]. This immune-modulatory mechanism of BCG was reported to limit the progression of autoimmune Type 1 Diabetes Mellitus (T1D) and Multiple sclerosis (MS).…”
Section: Introductionmentioning
confidence: 99%
“…In the past 10 years, clinical trials of adult BCG vaccination have shown therapeutic benefits for an array of disease – including a variety of allergic and autoimmune disease such as type 1 diabetes mellitus and multiple sclerosis [ [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] ]. Hence, we have hypothesized that BCG may help ameliorate the development of other autoimmune diseases that have been linked to mycobacteria [ 92 ]. Shown in Fig.…”
Section: Discussionmentioning
confidence: 99%